2018
DOI: 10.1111/ppe.12467
|View full text |Cite
|
Sign up to set email alerts
|

Motor performance in early life and participation in leisure‐time physical activity up to age 68 years

Abstract: BackgroundThis study examined associations between motor performance in early life and leisure‐time physical activity (LTPA) participation across adulthood, and whether these changed with age.MethodsData were from 2526 participants from the Medical Research Council National Survey of Health and Development. Motor indicators were mother‐reported ages at first standing and walking, teacher‐rated games ability at age 13, and finger‐ and foot‐tapping speed at age 15. LTPA was reported at ages 36, 43, 53, 60‐64, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…We found that later achievement of infant locomotor development milestones was significantly and positively associated with accelerometer‐measured light PA in women although the associations weakened after adjusting the models with adulthood lifestyle variables. Few studies have examined the association between infant motor development and adult PA 13,14 . Our findings are in accordance with a previous longitudinal study 14 that found limited evidence of association between age at first standing and walking and LTPA from age 36 to 68.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that later achievement of infant locomotor development milestones was significantly and positively associated with accelerometer‐measured light PA in women although the associations weakened after adjusting the models with adulthood lifestyle variables. Few studies have examined the association between infant motor development and adult PA 13,14 . Our findings are in accordance with a previous longitudinal study 14 that found limited evidence of association between age at first standing and walking and LTPA from age 36 to 68.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have suggested that earlier motor skill development is associated with higher PA levels during an individual's preschool, childhood, and adolescent years 11,12 ; however, less is known about the associations of early motor skill development with adulthood PA, and the evidence is inconclusive. For example, in a recent study of 34‐year‐old Finnish twins, earlier learning to stand unaided in infancy was associated with higher self‐reported leisure‐time PA (LTPA) in young adulthood, 13 whereas limited evidence was found between ages at reaching infant motor milestones and self‐reported LTPA in adulthood in the study of 1946 British birth cohort 14 . Only two studies had examined the association between motor development and accelerometer‐measured ST, and both were conducted in childhood, and the sample sizes were relatively small 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Given the association between motor performance and physical activity levels 5,6 and healthy weight status in children 6,28 , improving motor performance could be beneficial for health. Recent evidence shows that motor performance in children predicts physical activity levels three years later 22 , and that early life motor performance predicts engagement with sport and exercise throughout life to older adulthood 29 . Our results complement this finding, showing a positive association between participation in organized sport and motor performance, which remains when controlling for baseline motor performance.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Paediatric and Perinatal Epidemiology , Elhakeem et al describe a longitudinal cohort study of 2526 British participants born during the same week in 1946 and followed across their lifetime. In this cohort, teacher‐assessed better ability at games and measured faster finger‐ and foot‐tapping speed during adolescence were associated with higher participation in leisure‐time physical activity from age 36 to 68 years.…”
mentioning
confidence: 86%